PENYULUHAN TENTANG PENCEGAHAN KEJADIAN KECACINGAN PADA ANAK DI DESA PENEN KECAMATAN BIRU-BIRU - Bunga Mari Sembiring; Fithri Handayani Lubis (INSTITUT KESEHATAN DELI HUSADA, 2021)
From the results of the study, it turns out that the prevalence of worm disease is still high, namely 60-70%. This parasite is found all over the world. The frequency of this worm disease in Jakarta is quite high. In Bekasi, 1083 school children show a frequency of 24.4%. The incidence rate in Indonesia is still very high, namely almost all children aged 1-10 years have Ascariasis infection, while in adults it is estimated that 60% (in Jakarta). Indonesia still thrives on worm disease, the reason is that the personal hygiene of the community is still lacking. There are still many people who defecate on the ground, in rivers, in ditches, and on rice fields. Worm eggs can also be attached to major vegetables, that is, if the major vegetables are not cleaned using ditch water, river water and water that has been contaminated by worm eggs. Various factors that support the high rate of stomach infection pain in Indonesia are Indonesia's geographical location in the tropics which has a hot but humid climate, which allows stomach worms to breed well.